Relative´age effects. Implications for performer participation and development - Chapman, C.; Till, K. (sports coach UK, 2014)
Many sports use the academic year (1 September to 31 August) as the registration dates for entry into school, community, governing body talent pathways, and some professional competitions within the UK. While mirroring the educational system, these specific annual-age groups provide consistency for friendship groups and continuity for youngsters, and attempt to avoid large differences between children within sport to try to ensure equal competition and opportunities. However, this structure still leads to some children being almost one year older than others within the same annual-age group (eg a September birth compared to an August birth). This difference in age within an annual-age group is defined as relative age, with the consequences being the Relative Age Effect. The Relative Age Effect results in participation and selection differences favouring the relatively older participants and occurs in most youth sports, including football, rugby league, rugby union, basketball and tennis (Cobley et al, 2009). This means that a greater number of players born closer to the `cut-off` date of 1 September participate and are selected for teams, clubs and competitions. However, being relatively older may not be an advantage for all sports, with no Relative Age Effect shown in golf, and reversed Relative Age Effects favouring the relatively younger individual apparent in sports such as gymnastics. Relative Age Effects are evident in grass-roots sport from as early as the under-sevens age category through to the professional sporting arena. It is therefore essential that all people engaged in youth sports, from parents to coaches to talent pathway managers, are aware of the Relative Age Effect and the impact it can have on a participant`s development. Increasing awareness and educating all involved in the sporting landscape would enable more participants to firstly engage and secondly develop the skills necessary to be successful within their chosen sport(s). What follows is a consideration of three developmental periods in relation to the growth, maturation and development of children. Top tips on raising awareness of the Relative Age Effect and how to limit the effects associated with it (eg limited participation and [de]selection) are included.